Aplicação combinada de modelo e índice para avaliação de risco de segurança da água para consumo humano: estudo de caso da bacia hidrográfica do ribeirão pitanga (MG) - Corrêa, Rony Felipe Marcelino (Universidade Federal de São Carlos, 2024)
The safety of water for human consumption is everyone's right, it is directly related to people's quality of life and has an influence on the health of the population. Water safety risk assessment is a preventive measure, recommended by the World Health Organization, anticipating and mitigating problems and reducing corrective expenses to maintain water quality. The aim of this research was to apply a combined model and index to assess the safety risk of water for human consumption, carrying out a case study in the Bacia Hidrpgráfica do Ribeirão Pitanga (BHRP) in the State of Minas Gerais, municipalities of Inconfidentes, Bueno Brandão and Ouro Fino. The methodological phase of the research was divided into 4 main phases: (i) characterization of the study area; (ii) risk assessment with the Potencial Non-Point Pollution Index (PNPI); (iii) risk assessment with health inspection; (iv) analysis of water risk assessment results at BHRP. As a result, it was found that the dangerous events that create a risk to the safety of water for human consumption in the BHRP are related to the lack of adequate protection of the area and elements for collecting and storing water, allowing animal access and water contamination, mechanical and structural problems, such as clogging and breakdown of equipment, leaching of contaminants, and flooding events, causing supply problems. Risk assessment through sanitary inspection and through the use of an index were satisfactory for establishing the risk prioritization of water for human consumption in the BHRP. The integration of other water security risk assessment methods will enable water resource managers to have an integrated view of the river basin, contributing to the implementation of strategies to ensure water security.
Combined application of model and index to assess the safety risk of drinking water: case study of the pitanga river basin (MG)
Keywords: Recursos hídricos; Saneamento ambiental; Gestão de risco; Sensoriamento remoto; Geotecnologias; Water resources; Environmental sanitation; Risk management; Remote sensing; Geotechnologies; ENGENHARIAS::ENGENHARIA SANITARIA